Quality of clinical care in Bangladesh: skilled attendance index - Mahbub, Amina; Kamal, Faiza Ela (BRAC Research and Evaluation Division (RED), 2019)
The study was conducted to assess the quality of clinical care regarding skilled attendance in Bangladesh. The information was extracted from the delivery records in the facility with the aim of establishing a baseline regarding the situation at the facility and track progress towards achieving skilled attendance. In the study data was mainly collected from the last 6 month's case reports of District Hospital and Govt. MCWC of Kurigram district. Thus the study mainly dealt with 300 case reports of the facilities, but information was also taken from the delivery book, admission book and operation book of the facility. Among the cases 43% were complicated and 57% were uncomplicated. The delivery records clearly reflected poor record keeping system in the facilities. Study results revealed that at the facility level most of the key information was not recorded. No record was found about discharge diagnosis, duration of gestation at admission, presentation of foetus, time between delivery of baby and placenta, urine albumin and sugar. In some cases it was found that information regarding clinical status of woman at start of labour i.e. pulse, temperature, most recent haemoglobin level was recoded but was not compatible with the condition of the women. The limited availability of environmental factor like manpower were likely responsible for poor care records in the facility. Situation at Govt. MCWC, the obstetric service focused facility was found as better.